OPTIMASI STRATEGI ALGORITMA GREEDY UNTUK MENYELESAIKAN PERMASALAHAN KNAPSACK 0-1 - Paryati Paryati (Jurusan Teknik Informatika, 2009)
Knapsack is a place used to store an object with same or less size with its capacity. The objects can be put at entirely or partially. This analysis using knapsack 0 or 1, that is an object taken entirely or not at all. As for the profit value is benefit value that possessed by every object. In this analysis, we always expect optimal profit value from an object. But, more object doesn’t always mean more profit.